Sosialisasi Dana Pensiun Bagi Pelaku UMKM di Malioboro - Ahmad Syahrul Tarigan; Hasim As’ari (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This study promotes pension funds among MSMEs in Malioboro, Yogyakarta, to increase awareness and understanding of pension planning. Many MSMEs lack knowledge of pension funds, leading to inadequate financial preparation. Socialization methods, including seminars and brochure distribution, effectively conveyed information and increased awareness. Despite challenges, the study found a significant increase in awareness and interest in pension funds among MSMEs. Socialization is an effective way to increase awareness and understanding of pension funds among MSMEs, supporting their financial future.